Sustainable marketing and social intervention to encourage environmental care in the county of Valle de Bravo - Pilar Arroyo-López; Lorena Álvarez-Castañón (Ciencias Administrativas Teoría y Praxis)
This paper aimed to analyze a socio-ecological system in Mexico to design a social marketing strategy that encourages participation and induces behavioral change toward environmental protection. The methodological approach was participatory research. The main findings confirm a strong social indifference. There are low environmental concerns and low interest in knowing or adopting effective waste management or water savings practices because “the responsibility is of the government, not of the individuals”. Sustainable marketing offers a new perspective of the much-needed changes in the design of social interventions and public policies that lead civil society and businesses toward a stronger commitment to climate action.